Penerapan Metode The Extended Promethee II (EXPROM II) Dalam Pemilihan Pengangkatan Karyawan Baru Terhadap Mahasiswa Magang - Sri Poedji Lestari; Bernadus Gunawan Sudarsono (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Apprenticeship students are students who work and study directly at one of the companies they occupy according to the major they take, students who have done an apprenticeship and do a very good job at one of the companies will usually be proposed to be employees of the company, many students and from various universities participating in a company with the same department and in the selection must be done in a fair manner based on appropriate criteria and not based on who has family relations in a company, therefore it is necessary to make a selection involving a system, namely a decision support system where this system uses the extended promethee II method, this method is used to accumulate every value that each student candidate has that is supported by the company to become an employee, the results of the application of this method are king with the highest score who is the best candidate